Initial reaction mechanisms of cellulose pyrolysis revealed by ReaxFF molecular dynamics. (1st August 2016) - Zheng, Mo; Wang, Ze; Li, Xiaoxia; Qiao, Xianjie; Song, Wenli; Guo, Li
Graphical abstract: Highlights: Cellulose pyrolysis is simulated with large-scale models by GPU-based ReaxFF MD. Chemical mechanisms studied with the unique VARxMD for reaction analysis. Overall spectrum of product tendency and underlying detailed reactions revealed. Simulated product evolution (500–1400 K) agrees well with Py-GC/MS (673–1073 K). A reaction scheme for major pyrolyzates is obtained. Abstract: Mechanism investigation of cellulose pyrolysis is remarkably useful for efficient utilization of biomass. In this paper, a new methodology rooted in the first GPU enabled ReaxFF MD simulation program (GMD-Reax) and the unique cheminformatics based reaction analysis tool (VARxMD) was employed to investigate the initial reaction mechanism of cellulose pyrolysis. Both the overall spectrum product evolution and underlying detailed chemical reactions of cellulose pyrolysis have been revealed. A reaction scheme of cellulose pyrolysis with detailed reaction pathways for major pyrolyzates has been obtained that is not readily accessible by experiments. The simulated evolution tendencies of the major pyrolysis products (glycolaldehyde, levoglucosan and water) with temperature at 500–1400 K agrees well with the Py-GC/MS experimental observations at 673–1073 K. Compared with the large temperature discrepancy imposed by the widely used simulation strategy of artificially increased temperature in ReaxFF MD, the very close temperature range between the simulations and experiments suggests that cellulose is a good model system to validate the ReaxFF force field in predicting the behavior and chemistry events in pyrolysis of complex molecular systems. The computational approach of large model simulation facilitated by efficient computation of GMD-Reax, and chemical reaction analysis capability of VARxMD can shed new light on the detailed chemical mechanisms of pyrolysis for cellulose and other biomass.